Resilience, stress, and psychological well-being in nursing students: A systematic review - Li, Zhuang-Shuang; Hasson, Felicity (Nurse education today, 2020)
Synthesize the evidence relating to the interaction of resilience, stress, and well-being in undergraduate nursing students across countries. Systematic review Peer reviewed studies published from 2008 to December 2018 were searched in CINAHL, Web of Science, Medline (OVID), PsycINFo and four biomedical databases originating from China (China National Knowledge Infrastructure, WanFang Data, VIP and CMB). Adhering to the preferred reporting items for Systematic Reviews and Meta-analyses guidelines, eight databases were searched. Twelve studies, which met the inclusion criteria, were extracted, and subject to quality appraisal by two researchers. In total, 12 papers were included. Outcome analysis revealed the level of resilience as moderate; stress levels were high and the incidence of negative psychological health accounts for a proportion of nursing students. The interaction between resilience and stress and well-being was high. Resilience and low stress were found to better predict well-being. All the studies cited recommendations to inform educational policy and practice in relation to resilience, well-being, and stress among undergraduate nursing students. This was the first systematic review to synthesize the evidence relating to the interaction of resilience, stress, and well-being in undergraduate nursing students across cultural settings. Evidence confirms the importance of resilience in nursing students influencing stress and psychosocial morbidity. Nursing educational strategies that foster and enhance resilience is recommended.